2023
DOI: 10.1093/geronb/gbad057
|View full text |Cite
|
Sign up to set email alerts
|

Internalization or Dissociation? Negative Age Stereotypes Make You Feel Younger Now But Make You Feel Older Later

Abstract: Objectives Negative age stereotypes have negative, assimilative effects on the subjective aging experience due to internalization processes, but sometimes positive contrast effects are reported as well, reflecting dissociation and downward comparisons. Our aim was thus to compare short-term and long-term consequences of age stereotypes on the subjective aging experience, to test the hypothesis that contrast effects are visible cross-sectionally, whereas internalization processes are observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
1
1
Order By: Relevance
“…Moreover, prior research found a negative relationship between discrimination at work and respect towards older workers which, in turn, is associated with higher psychological well-being. In this study conversely, discrimination at work was associated with job insecurity which, in turn, was found to be associated with lower psychological well-being [47]. In conclusion, lower levels of discrimination at work were negatively associated with stress, insecurity, and the tendency to retire from work; and positively associated with appreciation of older employees, commitment to work, and life satisfaction.…”
Section: Introductioncontrasting
confidence: 40%
“…Moreover, prior research found a negative relationship between discrimination at work and respect towards older workers which, in turn, is associated with higher psychological well-being. In this study conversely, discrimination at work was associated with job insecurity which, in turn, was found to be associated with lower psychological well-being [47]. In conclusion, lower levels of discrimination at work were negatively associated with stress, insecurity, and the tendency to retire from work; and positively associated with appreciation of older employees, commitment to work, and life satisfaction.…”
Section: Introductioncontrasting
confidence: 40%
“…Depending on which standards of reference are chosen, the same objective aging status can result in positive or negative evaluations of one’s own aging. Variability in these processes can (partly) be explained by differences in age stereotypes that individuals have acquired earlier in life and that later become internalized and shape an individual’ views of their own aging [ 54 , 61 , 62 ]. These stereotypes also influence a person’s behavior (preparation for old age [ 63 , 64 ], physical activity [ 65 ]) and health [ 66 ], which feeds back into the sources of aging (see above).…”
Section: Aging: Objective Changes In Functioning and Their Subjective...mentioning
confidence: 99%